Tingkat Kepuasan Pasien Rawat Jalan Terhadap Pelayanan Kefarmasian Di Instalasi Farmasi Rumah Sakit Langit Golden Medika Sarolangun - Medi Andriani; Santi Perawati; Siti Nurhaliza (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Patient or customer satisfaction is the level of consumer feelings after comparing what he received and his expectations. The purpose of this study was to determine the level of satisfaction of outpatients with respect to pharmaceutical services at the pharmacy installation of Langit Golden Medika Sarolangun Hospital using 5 (five) dimensions of service quality, Reliability, Responsiveness, Assurance, Empathy, and Tangible Evidence This type of research is a descriptive non-experimental research. Observational data collection techniques with the criteria of outpatients and patients' families who redeem prescriptions, patients who can communicate well, and patients who can read and write. The results of these 5 (five) dimensions state patient satisfaction at a hospital pharmacy installation. This study was conducted by means of patients filling out questionnaires and then calculating the percentage of patient satisfaction with the indicators studied. Based on the calculation of the level of patient satisfaction on the Reliability indicator of 78.43%, the Responsiveness indicator of 80.13%, the Assurance indicator of 79.24%, the Empathy indicator of 80.76%, the Direct Evidence indicator of 79.22%.